THE OPTIMIZATION OF THE ROLE OF ZAKAT IN THE ALLEVIATING POVERTY IN INDONESIA - Haniefah, Farisha Rizky; Faozan, Akhmad (Journal of Economicate Studies, 2018)
This study aims to determine the extent of the role of zakat in alleviating identified as mustahiq inentrepreneurship. Zakat intended for mustahiq can be used as business capital where businessesdeveloped by mustahiq are generally still small-scale, which is not accessed by bank financialinstitutions. The mentoring process includes planning, implementing, supervising and controlling andevaluating the program, becoming one of the amil zakat programs in managing productive zakat so thatit is expected to create economic circulation, increase the productivity of community businesses,increase income / economic results, and be sustainable. The methodology used in this study is adescriptive qualitative method to see the effect of productive zakat on the empowerment of the poorthrough the poverty index. This study consisted of primary data and secondary data. Primary dataobtained from the survey results or the results of questionnaires and conducted in-depth interviews withproductive Zakat program managers in Baznas and mustahiq as participants of the communityempowerment program through productive zakat. While secondary data is obtained from the BAZNASProgram Report on the internet, several kinds of literature, articles both magazines, journals,newspapers and the internet. The results of the study show that overall mustahik considers that theproductive zakat program by Baznas has run very well.